Mycosis Fungoides in Skin of Color. Issue 6 (13th November 2022) - Rager, Taylor; Lake, Eden
ABSTRACT: Mycosis fungoides is the most common primary cutaneous T-cell lymphoma. Although mycosis fungoides affects patients of all skin tones, mycosis fungoides has a higher incidence in patients with skin of color. Patients with skin of color who are diagnosed with mycosis fungoides have worse outcomes and poor prognosis compared with patients with lighter skin tones. Mycosis fungoides is difficult to diagnose in patients with skin of color as rare subtypes or clinical presentations are commonly seen in these populations. Increased awareness of the presentation of mycosis fungoides in skin of color and early detection could address the higher rates of morbidity and mortality in these populations.